2020
DOI: 10.1080/21556660.2020.1734008
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of aceclofenac versus etoricoxib in the management of acute low back pain in a tertiary care hospital

Abstract: Background: The aim of management of acute low back pain is to alleviate the pain quickly and improve functional ability. Non-steroidal anti-inflammatory drugs are the first line of treatment. The challenge lies in deciding which NSAIDs will provide greater symptomatic relief, while also being cost-effective. Objective: To compare the effectiveness of aceclofenac and etoricoxib in the management of acute low back pain. Methods: This prospective, open label, observational study was conducted at a tertiary care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…In the study population of this trial, the age group mostly affected by LBP was 41-50 years, similar to that observed in earlier studies from India [14]. The results of this study are also in agreement with a recent report wherein LBP burden was shown to peak between 40 and 50 years, as well as data reported in GBD 2017 wherein YLDs were found to peak at 45-49 years of age [15].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the study population of this trial, the age group mostly affected by LBP was 41-50 years, similar to that observed in earlier studies from India [14]. The results of this study are also in agreement with a recent report wherein LBP burden was shown to peak between 40 and 50 years, as well as data reported in GBD 2017 wherein YLDs were found to peak at 45-49 years of age [15].…”
Section: Discussionsupporting
confidence: 92%
“…Age-standardized prevalence of LBP and YLDs was reported to be higher in females based on GBD 2017 [15]. A female preponderance was also observed in this study as well as in earlier studies on acute LBP [5,14] and in a systematic review from India [4].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…6 However, about 20% of acute LBP patients have persistent pain after 12 weeks and progress to chronic LBP. 7 According to the Global Burden of Disease 2016 Disease and Injury Incidence and Prevalence Collaborators, the number of years lived with disability of patients with LBP increased by 18% between 2006 and 2016. 8 In Germany, the annual direct medical expenses on LBP exceeded 7000 € per person.…”
Section: Introductionmentioning
confidence: 99%